The prior information influence on website choice in search engines - Souza, João Vicente Rosa de (2021)
This article discusses the importance and consequences of website positioning optimization in the results ranking in an internet search. Thus, an experiment was carried out consisting of a simulation of access to a research site together with a questionnaire, characterizing data collection as quantitative. The experiment was applied to 70 students from a college in the north of the state of Rio Grande do Sul. In this way, students from undergraduate courses in Business Administration and Law were invited to participate in the study. The results demonstrated the influence and relevant importance of prior information, proving to companies that this type of tool should be prioritized in the virtual commerce environment. It was also found that consumers who have less information about the product tend to visit the first sites listed as search results.